Cue-Reminders to Prevent Health-Risk Behaviors: A Systematic Review - van Leeuwen, Lonneke; Onrust, Simone; van den Putte, Bas; Kleinjan, Marloes; Lemmers, Lex; Engels, Rutger C. M. E.; Hermans, Roel C. J. (Frontiers in Public Health, 2019)
Introduction: It has been proposed that the use of cue-reminders may increase the effectiveness of interventions that aim to prevent health-risk behaviors (i.e., having unsafe sex, unhealthy dietary intake, lack of physical activity, and substance use). The aim of this systematic review was to explore whether there is evidence supporting this proposition, and to explore how cue-reminders are applied in health-risk behavior interventions to date. Method: We systemically reviewed (non-) randomized trials that examine differences in health-risk behaviors between an experimental group receiving an intervention with exposure to a cue-reminder and a control group receiving the intervention without such cue. Results: Six studies were eligible for inclusion. The studies differed in sample and research design, and how the cue-reminder was applied. One study demonstrated a positive and small effect, and one study found a negative medium effect of the cue-reminder. In the remaining studies, the effect sizes were positive but non-significant. Discussion: It is unclear whether complementing health-risk behavior interventions with cue-reminders increases the effectiveness of these interventions. Further investigation and experimentation into the efficiency and effectiveness of cue-reminders is needed before health-risk behavior interventions are complemented with cue-reminders.